Outcomes of the Ponseti Technique in Different Types of Clubfoot-A Single Center Retrospective Analysis - Maryum Naseer Butt; Wajida Perveen; Carmen-Iulia Ciongradi; Dan Iulian Alexe; Misbah Marryam; Laique Khalid; Daniel Lucian Dobreci; Ioan Sârbu (MDPI AG, 2023)
Background: Clubfoot is a congenital deformity that can affect one or both of a newborn's lower extremities. The main objective of the study is to evaluate and compare the outcomes of the Ponseti method for the management of different types of clubfoot. Methods: A retrospective analysis of 151 children with 253 clubfeet (idiopathic untreated, idiopathic recurrent, and syndromic) with at least one year of follow-up was conducted in four months after ethical approval. Data were collected with a structured proforma after the consent of the parents. An independent sample t-test was applied to show the comparison between the groups, and a p-value of 0.05 was considered significant. Results: Out of 151 patients, 76% were male and 24% were female. Out of a total of 235 feet, 96 (63%) were idiopathic untreated, 40 (26.5%) were idiopathic recurrent, and 15 (9.5%) were syndromic clubfoot. The average number of casts was higher in syndromic clubfoot (9 casts per foot). There was no significant difference in the baseline Pirani score of the three groups (p-value > 0.05); but after one year of follow-up, there was a significant difference in the Pirani score of idiopathic and syndromic clubfoot (p-value ≤ 0.05) and between recurrent clubfoot and syndromic clubfoot (p-value = 0.01). Conclusions: The aetiology of syndromic clubfoot affects the outcomes of the Ponseti method and leads to relapse. In idiopathic (untreated and recurrent) clubfoot, the Ponseti method does not produce a significant difference in outcome. Poor brace compliance and a lack of tenotomy lead to orthotic (ankle foot orthosis AFO and foot orthosis FO) use in the day time and the recurrence of clubfoot deformity in these three types of clubfoot.